2018
DOI: 10.1093/mnras/sty3344
|View full text |Cite
|
Sign up to set email alerts
|

Microlens mass determination forGaia’s predicted photometric events

Abstract: We used Gaia Data Release 2 to search for upcoming photometric microlensing events, identifying two candidates with high amplification. In the case of candidate 1, a spectrum of the lens (l1) confirms it is a usdM3 subdwarf with mass ≈ 0.11M , while the event reaches maximum amplification of 20 +20 −10 mmag on November 3rd 2019 (±1d). For candidate 2, the lens (l2) is a metal-poor M dwarf with mass ≈ 0.38M derived from SED fitting, and maximum amplification of 10 +40 −10 mmag occurs on June 3rd 2019 (±4d). Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The Einstein radius can also be obtained from the event timescale t E if the relative proper motion µ rel of the lens and the source are known, since θ E = µ rel t E (µ rel is the length of the µ rel vector). To date, however, there have only been a limited number of measurements of µ rel based on a detection of the luminous lens a decade or so after the event (e.g., Kozłowski et al 2007;Batista et al 2015;Beaulieu et al 2018;Bramich 2018;McGill et al 2018McGill et al , 2019. Moreover, this method would not work for dark lenses, except for known pulsars, as shown by, Dai et al (2010), Dai et al (2015) and Ofek (2018), among others.…”
Section: Introductionmentioning
confidence: 99%
“…The Einstein radius can also be obtained from the event timescale t E if the relative proper motion µ rel of the lens and the source are known, since θ E = µ rel t E (µ rel is the length of the µ rel vector). To date, however, there have only been a limited number of measurements of µ rel based on a detection of the luminous lens a decade or so after the event (e.g., Kozłowski et al 2007;Batista et al 2015;Beaulieu et al 2018;Bramich 2018;McGill et al 2018McGill et al , 2019. Moreover, this method would not work for dark lenses, except for known pulsars, as shown by, Dai et al (2010), Dai et al (2015) and Ofek (2018), among others.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, microlensing searches can help address limitations of more common observational methods and extend compact object observations to isolated objects without a binary companion. In the context of these searches, many studies have been performed to constrain the mass function of compact objects using observed photometric and astrometric microlensing events (Gould 2000;Wyrzykowski et al 2016;Sahu et al 2017;Ofek 2018;McGill et al 2019;Wyrzykowski & Mandel 2020;Mroz et al 2021). With the increasing number of microlensing surveys and improved monitoring of high stellar density regions like GCs, it should also be possible to obtain detailed information on the masses and kinematics of compact object populations in GCs.…”
Section: Discussionmentioning
confidence: 99%
“…This degeneracy means that physical interpretation of the event is ambiguous in the absence of further data. Some microlensing events deviate from the standard form, or can be predicted ahead of time, enabling the degeneracies to be wholly or partially lifted (e.g., Gould 1992Gould , 1994Bennett 1998;Evans 2003;McGill et al 2019a), though these exotica can be hard to pick out. In this paper, we direct our attention exclusively to standard PSPL events.…”
Section: Introductionmentioning
confidence: 99%